Bahasa Kritik sebagai Simbol Kekuasaan: Analisis Wacana Politik Dino Patti Djalal dengan Teori Semiotika Susanne Langer - Indah Gita Cahyani; David Wicaksono; Moh. Dey Prayogo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Public debate over President Prabowo Subianto's intensive overseas visits prompted criticism from Dino Patti Djalal that combined rational arguments with symbolic meanings. This study aims to analyze Dino Patti Djalal's critical language as a symbol of power using Susanne Langer's semiotic theory. A descriptive qualitative method with a semiotic approach was employed to examine four statements published on X/Twitter and reported by national media during May–June 2026. The data were analyzed through discursive and presentational symbols. The findings reveal that discursive symbols are reflected in empirical data, arguments on budget efficiency, diplomatic strategies, and the distribution of authority, while presentational symbols construct perceptions of accountability, leadership, efficiency, and political legitimacy. The study concludes that political language functions not only as a means of conveying information but also as a symbolic system that shapes public meaning through the integration of rationality and symbolic experience.